Aplicación de la metodología del taller de diseño en el fortalecimiento de la habilidad oral en la clase de ingles: diseño de estrategia oral en clase de ingles (2012)
Abstract. Learning a foreign language through the strengthening of own language skills such as are the oral, listening, writing and reading has involved a study and various positions on how to make these processes and skills are strengthened, some theories point to work together to sud skills abilities to strengthen the learning, some others are based only on vocabulary acquisition and commissioning of the same context focusing on the written and oral. All times postulate learning and strengthened some pedagogical and classroom strategy also raises the roles of student, teacher and assessment models. This together with the methodology that has raised the Design Workshop and the way the teacher taught teach design and thinking modes in problems which require a process to reach an assertive and creative solution be it a product or idea has done, students strengthen their reflective thinking and a constant search for unique solutions and practices.